Hush - Woodson, Jacqueline (New York Puffin Books, 2010)
Twelve-year-old Toswiah finds her life changed when her family enters the witness protection program.
First published in the United States of America by G.P. Putnam's Sons, a division of Penguin Young Readers Group, 2002
A Newbery Honor Book
UCWS-2014-G-1639 donated by Prof. Eric Julian Manalastas
Keywords: Witnesses -- Protection -- Fiction; African Americans -- Fiction; Jehovah's Witnesses -- Fiction